Skrining Kejadian Stunting Melalui Pemeriksaan IMT Pada Peserta Didik Sekolah Dasar di Desa Balang Baru, Kecamatan Tarowang, Kabupaten Jeneponto - Nurhikmah; Bellona Mardhatillah Sabillah; Muh. Khaedar; Selpi Alpita; Muh. Adnan. M; Saparuddin Latu (INTEGRATIF: Jurnal Pengabdian Kepada Masyarakat, 2026)
Stunting is a growth failure condition in children caused by long-term chronic malnutrition that may affect physical growth, cognitive development, activity, and immune function. Early detection of nutritional status among school-age children can be conducted through anthropometric measurements, including body weight and height, followed by Body Mass Index (BMI) calculation as an initial screening method. This community service activity aimed to describe the nutritional status and potential risk of stunting among elementary school students in Balang Baru Village, Tarowang District, Jeneponto Regency. The activity involved 215 students from three elementary schools, consisting of 16 students from SDN 9 Tarowang, 85 students from SDN 18 Tarowang, and 114 students from SDN 15 Tarowang. The methods included partner coordination, body weight and height measurement, BMI calculation, nutritional status classification, and descriptive analysis using frequency and percentage. The results showed that 155 students (72.09%) had normal nutritional status, 42 students (19.53%) were classified as underweight, and 18 students (8.37%) were classified as overweight. These findings indicate that most students had normal nutritional status; however, underweight students still require further monitoring as part of early stunting prevention through school- and community-based efforts.